Molecular basis of the nitrogen response in plants. Issue 4 (4th July 2017) - Ueda, Yoshiaki; Konishi, Mineko; Yanagisawa, Shuichi
ABSTRACT: Nitrogen is an essential element for living organisms because it is a crucial constituent of biomolecules. Inadequate supply of usable nitrogen reduces plant growth and crop yield. The primary nitrogen sources for plants are nitrate and ammonium in soils, and plants have multiple layers of sensing and adaptive mechanisms that respond to the availability of these nutrients. The adaptive responses are called 'nitrogen responses, ' which include morphological and physiological responses enabling plants to efficiently take up nitrogen and adapt to spatiotemporal fluctuations in nitrogen abundance in the field. In this review, we summarize the strategies that plants use to respond to changes in the nitrogen nutrient status in the soil and discuss different effects produced by nitrate and ammonium, emphasizing the important role of nitrate for plant growth. Recent studies revealed the molecular mechanism mediating the primary response to nitrate provision and the molecular mechanisms that coordinate the nitrogen response with responses to another macronutrient, phosphorus. We thus discuss these molecular mechanisms as well.